6. Multiply: \( (x+3)\left(4 x^{2}+6 x+8\right) \)
Real Tutor Solution
Answer
Solution
Reviewed and approved by the UpStudy tutoring team
Mind Expander
To solve the multiplication \( (x + 3)(4x^2 + 6x + 8) \), we can use the distributive property, also known as the FOIL method. We distribute \( (x + 3) \) to each term inside the parentheses: 1. \( x \times 4x^2 = 4x^3 \) 2. \( x \times 6x = 6x^2 \) 3. \( x \times 8 = 8x \) Now for the \( 3 \): 4. \( 3 \times 4x^2 = 12x^2 \) 5. \( 3 \times 6x = 18x \) 6. \( 3 \times 8 = 24 \) Now we combine all these terms: \[ 4x^3 + 6x^2 + 8x + 12x^2 + 18x + 24 \] Combine like terms: - For \( x^2 \): \( 6x^2 + 12x^2 = 18x^2 \) - For \( x \): \( 8x + 18x = 26x \) Thus, we get: \[ 4x^3 + 18x^2 + 26x + 24 \] So the final answer is: \( \boxed{4x^3 + 18x^2 + 26x + 24} \)